Anti-Inflammatory, ACE Inhibitory, Antioxidative Activities and Release of Novel Antihypertensive and Antioxidative Peptides from Whey Protein Hydrolysate with Molecular Interactions. Issue 4 (19th May 2023) - Mansinhbhai, Chaudhari Hiralben; Sakure, Amar; Liu, Zhenbin; Maurya, Ruchika; Das, Sujit; Basaiawmoit, Bethsheba; Bishnoi, Mahendra; Kondepudi, Kanthi Kiran; Padhi, Srichandan; Rai, Amit Kumar; Mishra, Birendra K.; Hati, Subrota
Abstract: Objective: The aim of the study was to evaluate the whey protein hydrolysate with bio-functional attributes viz. antioxidative, anti-inflammatory and ACE inhibition efficacy and release of bioactive peptides with antioxidative and ACE-inhibitory activity by employing Pepsin. Method: The antioxidant, Anti-inflammatory, ACE inhibitory and proteolytic activities of the whey protein hydrolysates were studied followed by SDS-PAGE analysis and IEF. Anti-inflammatory activity of whey protein hydrolysate was also studied on RAW 264.7 cell line. The separation of the bioactive peptides from whey protein hydrolysate was achieved by RP-HPLC. The purified bioactive peptides were identified and characterized using RPLC/MS. Results: WPC (Whey protein concentrate) hydrolysate with pepsin showed proteolytic activity ranging between 14.46 and 18.87 mg/ml. Using the ABTS assay, the highest antioxidative activity was observed in 10 kDa retentate (84.50%) and 3 kDa retentate (85.96%), followed by the highest proteolytic activity (13.83 mg/ml) and ACE inhibitory activity (58.37%) in a 5% WPC solution at 65 °C after 8 h of pepsin hydrolysis. When the protein hydrolysate concentration was low, the production of proinflammatory cytokines by lipopolysaccharide-treated murine macrophages (RAW 264.7) was reduced. SDS-PAGE results exhibited very little protein bands when comparing with WPC hydrolysates to insoluble WPC. There were no protein spots on 2 D gel electrophoresis and "in-solution trypsin digestion" technique have been utilized to digest protein samples directly from WPC hydrolysates. Novel antioxidative peptides and ACE inhibitory peptides were also observed by comparing two databases, i.e., BIOPEP and AHTPDB respectively. The peptide sequences used in this study were found to have excellent potential to be used as inhibitors of hACE as all of them were able to show substantial interactions against the enzyme's active site. Conclusions: The antihypertensive and antioxidative peptides from whey protein hydrolysates may be beneficial for the future development of physiologically active functional foods. Further, in vivo investigations are required to establish the health claim for each individual bioactive peptide from whey protein hydrolysate. Supplemental data for this article is available online at